Clinical course and prognosis of dilated cardiomyopathy in children - Hirapur, Iranna S.; Rajendran, Ravindran; ., Jayaranganath; Nanjappa, Manjunath (International Journal of Research in Medical Sciences, 2019)
Background: Epidemiology and clinical course of dilated cardiomyopathy (DCM) in children and infants are not well established. Thus, this study aims to investigate the clinical course and prognosis of DCM in children Methods: This was a single-center, prospective, observational study conducted at a tertiary-care center in India between February 2011 and September 2012. A total of 31 patients admitted to the paediatric department diagnosed with DCM were included in the study. Patients were divided into three groups based on the age at the time of diagnosis: 0-3 years, >3-12 years and >12-16 years. Among the study population, 28 patients were followed up for a mean period of 1.44 years and three patients were lost to follow-up. Results: Of the 31 patients, 11 patients were male with a mean age of 8.9±6 years and 20 patients were female with a mean age of 8.3±6 years. All patients were presented with same characteristics of New York heart association (NYHA) class III-IV dyspnoea and fatigue. Among 28 patients who were followed-up for a mean period of 1.44 years, 20(71.4%) patients died and eight patients were on follow up. Of the eight patients, five patients were with NYHA class III symptoms and three patients were with NYHA class I-II symptoms. Conclusions: Dilated cardiomyopathy in children is a very serious disease with a grave prognosis. Patients with NYHA III-IV symptoms have a very high mortality rate and potential use of other therapies remains to be fully evaluated in paediatric population.